If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
33*(x+2/5) = x-(1/3) // - x-(1/3)
33*(x+2/5)-x+1/3 = 0
(3*33*(x+2/5))/3+(3*(-x))/3+1/3 = 0
3*33*(x+2/5)+3*(-x)+1 = 0
96*x+1+198/5 = 0
96*x+203/5 = 0
(96*x+203/5)/3 = 0
(96*x+203/5)/3 = 0 // * 3
96*x+203/5 = 0
96*x+203/5 = 0 // - 203/5
96*x = -203/5 // : 96
x = -203/5/96
x = -203/480
x = -203/480
| 10.35(3)(15)=465.75 | | x^2+y^2+10x+12y+61=0 | | -4x+6=3x+-8 | | 1000/9.81 | | 52-3x=24x+16 | | 1+x^4-2x^2+1.96x^2=1.0096x^4 | | -6x+7=10-5x | | 60+.6x=.8x | | (w+8)(w-3)=0 | | 60+.6=.2 | | 5x+10=64-4x | | 5y^2+9=3y | | y^2=6y+7 | | 6x+13=35-3x | | (3d+2)(7-1)=0 | | -4x-10=46+5x | | (1/3x)=9 | | 4x+1=60 | | 5x-16=4x+5 | | x-10=-21+2x | | x^2=5+4x | | x+7=-0 | | 5+7=3x | | x^2=y^4-77 | | y=5-8x | | 12x-10=4x-5 | | 2x+3=33+7x | | (-3y^2-8y)+(6y^2+y-9)= | | 18(4/9) | | -4/7+2/5u=-1/2 | | -4+7x=x+20 | | 9x+6=3x-2 |